(3CSGSjGJ GdHQeLI HGSJYeGd (BVisual Basic.net /s - (3YRH, YRH eMeOs ((3GdbGgQI(B: s (3OGQ GdcJH GdYdejI ddfTQ hGdJhRjY(B, s, 2004)
(3ebOeI Yf (Bvisual studio.net - (3eQHY GdGOhGJ (Btool box- (3bhGYO GddZI(B- (3NGUjI GdJhQjK (Binheritance- (3ebOeI Yf bhGYO GdHjGfGJ (Bintroduction to datadbase- (3eYGdLI GdGNWGA (Bdebugs
Keywords: (3GdHQeLjGJs; (3Yde GdMGShHs; Visual Basic.net